Nilai Keindahan Tari Ranggawis Karya Susiati di Sanggar Wisanggeni Kabupaten Purbalingga - Salwa Risma Nurriskiani; Joko Wiyoso (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the aesthetic values of Ranggawis Dance as a form of regional creative dance that develops in Purbalingga Regency. This research employs a qualitative method with a descriptive approach, supported by a choreographic aesthetic approach. The theoretical framework used is the aesthetic theory proposed, which includes aspects of form, content, and performance. Data collection techniques were carried out through observation, interviews, and documentation involving choreographers, musicians, dancers, and related parties in the performance of Ranggawis Dance. The data were analyzed descriptively using a qualitative approach by linking field findings with the applied aesthetic concepts. The results show that the aesthetics of Ranggawis Dance are formed through the harmony of form aspects, including movement, musical elements, and dancer composition; content aspects reflecting values of togetherness and joy within the community; and performance aspects demonstrated through synchronization (rampak) and dancers’ expressions. The dance movements, which combine Banyumasan, Jaipong, and contemporary elements, create a dynamic and harmonious impression, while the use of pentatonic scales strengthens the traditional character. The collaborative creative process between choreographers and musicians also contributes to the overall aesthetic unity of the performance. Therefore, Ranggawis Dance possesses strong aesthetic values, reflects local cultural identity, and has the potential to be further developed as part of traditional art preservation.